Epworth League Convention at Humboldt - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of young people, mostly teenagers and children. Prominent banners in the picture include: "Ferndale", "Salinas", "Napa", "ARKTA", "Grace", "Fortuna League", "Oroville", "Wood Empire", "Corning", and "Redding". A small child with crutches holds a "Redding Riots" sign in front of the Redding banner. There is some damage to the far left and bottom edge of the photograph due to the degredation of the original nitrate film.